2012
DOI: 10.1007/978-3-642-28601-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Corpora for WordNet Construction: Machine Translation vs. Automatic Sense Tagging

Abstract: Abstract. In this paper we present a methodology for WordNet construction based on the exploitation of parallel corpora with semantic annotation of the English source text. We are using this methodology for the enlargement of the Spanish and Catalan versions of WordNet 3.0, but the methodology can also be used for other languages. As big parallel corpora with semantic annotation are not usually available, we explore two strategies to overcome this problem: to use monolingual sense tagged corpora and machine tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…It is usually used for the words translation such as in Ref. [10]. When translating the sentences, the results are usually blur, shift.…”
Section: Related Workmentioning
confidence: 99%
“…It is usually used for the words translation such as in Ref. [10]. When translating the sentences, the results are usually blur, shift.…”
Section: Related Workmentioning
confidence: 99%
“…However, this kind of corpus is not easily available in most languages. In the research, which was conducted by Oliver and Climent (2012), two strategies for the automatic construction of these corpora are proposed: (i) by the machine translation of sense-tagged corpora, and (ii) by the automatic sense tagging of bi-lingual word-aligned corpora. The results for Spanish language showed that the first strategy works better than the second.…”
Section: Related Workmentioning
confidence: 99%
“…These methods are usually divided into merge and expansion approaches (Fellbaum & Vossen, 2012;Oliver & Climent, 2012;Erjavec & Fišer, 2006). However, there are methods that combine the merge and expansion models and benefit from the advantages of both approaches (Prabhu, Desai, Redkar, Prabhugaonkar, Nagvenkar, & Karmali, 2012;Apidianaki & Sagot, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wordnets, except the PWN, have been usually constructed by one of two approaches. The first approach translates the PWN to T (Bilgin et al, 2004), (Barbu and Mititelu, 2005), (Kaji and Watanabe, 2006), (Sagot and Fišer, 2008), (Saveski and Trajkovsk, 2010) and (Oliver and Climent, 2012); while the second approach builds a Wordnet in T, and then aligns it with the PWN by generating translations (Gunawan and Saputra, 2010). In terms of popularity, the first approach dominates over the second approach.…”
Section: Introductionmentioning
confidence: 99%